Carapace length-weight and width-weight relationships of Scylla serrata in Bulungan District, North Kalimantan, Indonesia - BAMBANG WIDIGDO; RUKISAH RUKISAH; ASBAR LAGA; AGUS A. HAKIM; YUSLI WARDIATNO (Biodiversitas Journal of Biological Diversity, 2017)
Widigdo B, Rukisah, Laga A, Hakim AA, Wardiatno Y. 2017. Carapace length-weight and width-weight relationships of Scylla serrata in Bulungan District, North Kalimantan, Indonesia. Biodiversitas 18: 1316-1323. The mud crab, Scylla serrata lives associated with mangrove ecosystems and is widely distributed in the Indo West-Pacific. The present work was aimed to reveal the carapace length/width-weight relationships of Scylla serrata in two mangrove ecosystem area of Bulungan District, North Kalimantan- Indonesia, i.e. Kahayan Delta and Tibi Island. The crabs were collected by using ambau pancang (trap) for two months from November to December 2016. A total of 522 individuals were collected and their carapace length, carapace width, and weight were measured. The sex ratio of total collected samples (male to female) was 1:0.79. Carapace length and width of S. serrata caught in these two study area ranged from 40 to 89 mm for male; 32 to 91 mm for female and 59 to 128 mm for male; 53 to 122 mm for female, respectively. The carapace length-weight relationships of total samples showed logarithmic equations as follow: W = -3.2194 + 2.9725 Log CL for male and Log W = -2.2010 + 2.3750 Log CL for female. While the carapace width-weight relationships are as follow: W = -3.9162 + 3.1012 Log CW for male and Log W = -2.6001 + 2.3968 Log CW for female. The b values of carapace width-weight relationship indicated that the growth pattern of male was positive allometric and female was negative allometric. Size frequency of crab population is also presented.